Bispyrrolylbenzene Anion Receptor: From Supramolecular Switch to Molecular Logic Gate. Issue 40 (1st September 2014) - Granda, Jarosław M.; Staszewska‐Krajewska, Olga; Jurczak, Janusz
Abstract We have designed anion receptor 4 based on a conformationally labile bispyrrolylbenzene framework, the conformation of which can be changed by appropriate anionic stimuli. In the absence of fluoride anion, the pyrrole moieties rotate freely at room temperature. However, when the concentration of fluoride anion exceeds 2 equivalents, the rotation of the pyrrole units slows down and the conformation of the receptor changes to anti‐anti. DFT calculations have shown that this change is due to binding of a third fluoride anion through CH interaction. Anion receptor 4 can also serve as a molecular logic gate. Anionic inputs such as fluoride and dihydrogenphosphate allow the realization of INHIBIT and NAND logic gate functions with absorption and fluorescence as readouts, respectively.